From harvest to consumer - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Postharvest: an introduction to the physiology and handling of fruit, vegetables and ornamentals. Fourth edition. R Wills, B McGlasson, D Graham and D Joyce. 1998. 262 pp. ISBN 0 86840 560 4 (UNSW Press) ISBN 0 85199 264 1 (CABI)